PENEGASAN KARAKTER PSIKOLOGIS TOKOH SURYANI MELALUI KOSTUM PADA FILM PENYALIN CAHAYA KARYA WREGAS BHANUTEJA - Dewita, Mutiara (Offscreen, 2024)
This study examines the Light Copying Film that raises the teme against injustice. This research aims to analyze the psychological character of Syriac characters in the Light Copying Film through the use of costumes. The method used was a descriptive qualitative analysis of the costume changes Syriac wore throughout the film. This study uses the theory of mise en scene, color psychology, and character 3D analysis to reveal the relationship between costume changes and Syriac psychological dynamics, research results suggest that costumes play an important role in describing the psychological development of Syriac characters. The choice of colors, textures, and costume styles consistently reflects the emotional state, internal conflicts, and character travel from stress to self-empowerment. The dominant dark and neutral colors at the beginning of the story indicate a somber mood and a sense of alienation, while the transition to lighter colors indicates a Syriac attempt to escape psychological distress. The character's 3D approach also highlights the relationship between costumes and Syriac interactions with the environment as well as other characters in the narrative. These results can serve as a reference for filmmakers in optimizing visual aspects to strengthen psychological characterization in cinema. Keywords: Injustice Psychological Character, Costume, Light Copier, Descriptive Qualitative, Suryani.